2002
DOI: 10.1002/jemt.10228
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian acetylcholine and muscarinic receptors: Hints of a novel intrinsic ovarian regulatory system

Abstract: More than two decades ago, the degrading enzyme of the neurotransmitter acetylcholine (ACH) was reported in nerve fibers of the rat ovary. Subsequently, it was assumed that ACH is a neurotransmitter of ovarian nerves, although the sole presence of the degrading enzyme, ACH-esterase, does not allow such a conclusion. That ACH may be involved in the complex regulation of ovarian functions, including hormone production, was indicated by studies using, for example, granulosa cells (GCs). The lack of detailed infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
(59 reference statements)
2
40
0
Order By: Relevance
“…It has been suggested that acetylcholine may play a role in the cellular proliferation (Gutkind et al 1991) and in the changes of the constantly remodelling ovarian tissue histoarchitecture (Lauder & Schambra 1999, Mayerhofer & Fritz 2002, both of which occur in this oestrous stage. It has also been described that cholinergic agents modify the secretion of hormones from human granulosa cells in culture (Bodis et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that acetylcholine may play a role in the cellular proliferation (Gutkind et al 1991) and in the changes of the constantly remodelling ovarian tissue histoarchitecture (Lauder & Schambra 1999, Mayerhofer & Fritz 2002, both of which occur in this oestrous stage. It has also been described that cholinergic agents modify the secretion of hormones from human granulosa cells in culture (Bodis et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Groups of six animals in oestrus (E) were used for the experimental procedure. This stage was chosen for three important reasons: first, because it is the period of the oestrous cycle when there is more ovarian irrigation, and the increased values of oestrogen cause a rapid dilation of blood vessels by activating endothelial NOS (Acosta & Miyamoto 2004); secondly, because the ONP fibres are mainly perivascular (Lawrence & Burden 1980) and could take part in the vascularization changes that occur in this stage; and thirdly, because it is a stage of deep biochemical and structural changes (Mayerhofer & Fritz 2002). The experiments were performed according to the procedures approved in the UFAW Handbook on the Care and Management of Laboratory Animals (Poole 1999) and the Guide for Animal Use and Handling of the National University of San Luis, Argentina.…”
Section: Animalsmentioning
confidence: 99%
“…Mayerhofer and Fritz, 2002). This includes the situation for human keratinocytes, which are reported to synthesize, store, release and degrade ACh (Grando et al, 1993b).…”
Section: Tenocytes Might Be a Source Of Ach Productionmentioning
confidence: 99%
“…On the basis of the findings of the present study it can be asked whether cholinergic influences take a part in these events. From this point of view it is of interest to note that cholinergic stimulation of the mAChRs (M 1 and M 5 ) of the human granulose cells leads to increased cell proliferation of these cells in vitro (Mayerhofer and Fritz, 2002). ACh has also been shown to markedly stimulate the proliferation of myofibroblastic hepatic stellate cells and to induce collagen gene expression in these cells (Oben et al, 2003).…”
Section: Receptors In Relation To Bloodmentioning
confidence: 99%
“…well-known effects on angiogenesis (Jacobi et al, 2002;Cooke et al, 2007). It is also known that an increased cell proliferation occurs in response to cholinergic stimulation (Mayerhofer & Fritz, 2002;Metzen et al, 2003;Oben et al, 2003). That includes proliferative effects on human fibroblasts .…”
Section: Functions Of Non-neuronally Produced Achmentioning
confidence: 99%